Post-reform development in Asia essays for Amiya Kumar Bagchi - Bagchi, Amiya Kumar; Sanyal, Manoj Kumar; Sanyal, Mandira; Amin, Shahina (Hyderabad Orient Blackswan, 2009)
Contributed articles on poverty and inequality in China, India, and Bangladesh.
Poverty, inequality and development state in China Inequality and poverty in China in the post reform period/ Azizur Rahman Khan China and the human development state/Carl Raskin Food insecurity, poverty and employment in India Food insecurity, undenourishment and poverty in India during the 1990s/ Ranjan Ray Higher growth, lower poverty and higher unemployment/Sanjay K. Hansda and Partha Ray Poverty as a determinant of children's market work and household work in Bangladesh/Shahina Amin, Shakil Quayes and Janet Rives Gender and labour: post- reform scenario in India/ Panchanan Das,Byasdeb Dasgupta and Padip Kumar Biswas Land Tenure reforms
Includes statistical tables.
Keywords: NEOLIBERALISM; POVERTY; EQUALITY